Sacred Tensions: How Mental Health Professionals Navigate Spirituality, Ethics, and Professional Identity - Tunç, M. Furkan (Pastoral psychology, 2025)
This study explores the ethical dilemmas and professional identity challenges faced by mental health professionals who integrate spirituality into their therapeutic practice, focusing on the Turkish cultural context. Employing a qualitative phenomenological design, the study conducted in-depth, semi-structured interviews with eight practitioners specializing in guidance and psychological counseling, psychology, or psychiatry. Findings highlight the nuanced balance therapists must strike between respecting clients’ spiritual values and maintaining professional boundaries. Participants emphasized the importance of cultural humility, client autonomy, and ethical reflexivity when navigating faith-related conflicts. The study also identified tensions between Western ethical standards and local practices, underscoring the need for culturally contextualized guidelines. The research contributes to the literature by addressing gaps in culturally specific ethical frameworks and offering practical insights for spiritually integrated therapy. This study advocates for a client-centered, pluralistic approach that honors spiritual diversity while upholding professional integrity in mental health practice.